1999
DOI: 10.1002/stem.170265
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between IL‐3 Receptor Expression and Growth Potential of Human CD34 + Hematopoietic Cells from Different Tissues

Abstract: CD123 (␣-subunit of IL-3 receptor) expression on primitive and committed human hematopoietic cells was studied by multicolor sorting and single-cell culture. The sources of cells included fetal liver (FLV), fetal bone marrow, umbilical cord blood, adult bone marrow and mobilized peripheral blood. Three subsets of CD34 + cells were defined by the levels of surface CD123: CD123 negative , CD123 low , and CD123 bright . Coexpression of lineage markers showed that a majority of CD34 + CD123 bright cells were myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…IL-3 is an early cytokine that supports proliferation and differentiation of HSCs as well as primitive multipotent and myeloid progenitors (27)(28)(29), whereas the receptor tyrosine phosphatase CD45, and presumably its CD45RA isoform, can negatively regulate at least some classes of cytokine-receptor signaling (30). Several previous studies have been communicated concerning the surfaceantigen expression of early myeloid progenitor cells in humans (3,6,(9)(10)(11)(12). It was shown that CD34 ϩ CD45RA ϩ cells are devoid of erythroid and enriched for granulocyte and macrophage progenitor cells (6,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-3 is an early cytokine that supports proliferation and differentiation of HSCs as well as primitive multipotent and myeloid progenitors (27)(28)(29), whereas the receptor tyrosine phosphatase CD45, and presumably its CD45RA isoform, can negatively regulate at least some classes of cytokine-receptor signaling (30). Several previous studies have been communicated concerning the surfaceantigen expression of early myeloid progenitor cells in humans (3,6,(9)(10)(11)(12). It was shown that CD34 ϩ CD45RA ϩ cells are devoid of erythroid and enriched for granulocyte and macrophage progenitor cells (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that CD34 ϩ CD45RA ϩ cells are devoid of erythroid and enriched for granulocyte and macrophage progenitor cells (6,10). Also, different levels of IL-3R␣ expression on CD34 ϩ cells reportedly are associated with preferential lineage readout, as IL-3R␣ Ϫ cells are enriched for erythroid, IL-3R␣ lo cells for multipotent, and IL-3R␣ ϩ cells for granulocyte͞macrophage colony-forming cells (9). However, in those studies early lymphoid cells, lineage low or positive cells, and͞or HSCs and multipotent progenitors within the CD34 ϩ fraction were not excluded by using negative or positive markers, likely resulting in heterogeneous populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the less mature erythroid progenitors, MEP, at the point of lineage restriction from CMP, prior to GPA expression, we examined the change during culture of the previously defined markers interleukin-3 receptor (IL-3R/CD123) and Fmslike tyrosine kinase 3 (Flt-3/CD135), which are present at low levels on CMP and GMP and absent on MEP isolated from human bone marrow and cord blood. 27,31,32 Surface levels of both markers increase over the first two days in culture and then decrease to Day 4 on the bulk population, so they do not provide useful markers for early lineage restriction in erythroid culture ( Figure 1B). The erythroid marker CD36 was originally identified as a cell surface marker of erythroblasts 33 and later shown to be detectable prior to the appearance of the erythroid differentiation marker GPA.…”
Section: Cd36 Expression Marks Megakaryocyte/erythroid Restricted Promentioning
confidence: 99%
“…Cells were sorted by FACS 33 to produce cell populations and pure subclones with different levels of nephrin expression. Sorting was …”
Section: Fluorescence-activated Cell Sorting (Facs) Of Cells Showing mentioning
confidence: 99%